Immunomodulation in Human Dendritic Cells Leads to Induction of Interferon-Gamma Production by Leishmania donovani Derived KMP-11 Antigen via Activation of NF-κB in Indian Kala-Azar Patients. (22nd January 2014) - Chaudhary, Rajesh; Amit, Ajay; Yadav, Anupam; Singh, Anurag; Kumar, Vikash; Singh, S. K.; Narayan, Shyam; Rabidas, Vidyanand; Pandey, K.; Kumar, Anil; Das, Pradeep; Bimal, Sanjiva
Abstract : Dendritic cells (DCs) and macrophages (MΦ s) are well-known antigen presenting cells with an ability to produce IL-12 which indicates that they have potential of directing acquired immunity toward a Th1-biased response. The aim of this study was to examine the effect of Leishmania specific KMP-11 antigen through comparison of immune responses after presentation by DCs and MΦ s to T cells in Indian patients with VL. Patients with DCS and MΦ s were directed against a purified Leishmania donovani antigen (KMP-11) and phytohaemagglutinin (PHA). The cytokines (IL-12, IL-10, and TGF-β ) producing abilities of the DCs and MΦ s against these antigens were determined by flow cytometry. The transcription factor (NF-κ B) and T-cell cytokine support (IFN-γ, IL-10), which could be significant in effector immune function, were also determined. Severe hindrance in the immune protection due to Leishmania parasites, as revealed by decreased expression of IL-12 and upregulation of IL-10 and TGF-β expression in the MΦ s compared to DCs, occurred in VL patients. The production of IL-12 in response to L. donovani KMP-11 antigen was increased in DCs which was reduced in MΦ s of VL patients. In contrast, the presentation of KMP-11 antigen by DCs to T-lymphocytes in VL patients significantly increased the IFN-γ produced by these immune cells, whereas the levels of IL-10 were significantly elevated after presentation of KMP-11antigen by MΦ s. The VL patients were observed with severely dysfunctional MΦ s in terms of NF-κ B activity that could be recovered only after stimulation of DCs with L. donovani KMP-11 antigen. Immunologically the better competitiveness of KMP-11 antigen through a dendritic cell delivery system may be used to revert T-cell anergy, and control strategy can be designed accordingly against kala-azar.